2019
DOI: 10.1002/jcla.23097
|View full text |Cite
|
Sign up to set email alerts
|

Soluble urokinase plasminogen activator receptor associates with higher risk, advanced disease severity as well as inflammation, and might serve as a prognostic biomarker of severe acute pancreatitis

Abstract: Background This study aimed to explore the potential of soluble urokinase plasminogen activator receptor (suPAR) as a biomarker for severe acute pancreatitis (SAP) risk prediction and disease management in SAP patients. Methods Totally 225 acute pancreatitis (AP) patients (including 75 SAP, 75 moderate‐severe acute pancreatitis [MSAP], and 75 mild acute pancreatitis [MAP] patients) were recruited based on the Atlanta classification, and their serum samples were obtained within 24 hours after admission. Meanwhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 20 publications
2
28
0
Order By: Relevance
“…The association between these indicators and severity of AP was reported to be controversial. Some studies proved that age increases with AP severity, 56 , 57 while other cohort studies reported no significant difference in age between non‐SAP and SAP, 58 , 59 , 60 which is also consistent with our current study and previous cohort study of 238 AP patients. 61 Furthermore, central obesity, hypertriglyceridemia (HTG), hypertension (HT), and diabetes mellitus (DM), a set of comorbidities termed metabolic syndrome (MetS), 62 were also reported ambiguous correlation with SAP.…”
Section: Discussionsupporting
confidence: 93%
“…The association between these indicators and severity of AP was reported to be controversial. Some studies proved that age increases with AP severity, 56 , 57 while other cohort studies reported no significant difference in age between non‐SAP and SAP, 58 , 59 , 60 which is also consistent with our current study and previous cohort study of 238 AP patients. 61 Furthermore, central obesity, hypertriglyceridemia (HTG), hypertension (HT), and diabetes mellitus (DM), a set of comorbidities termed metabolic syndrome (MetS), 62 were also reported ambiguous correlation with SAP.…”
Section: Discussionsupporting
confidence: 93%
“…The expression of uPAR is up-regulated in activated immune cells, which in turn results in increased suPAR levels [ 18 ]. This has been reported consistently in studies showing that increased suPAR is associated with systemic inflammation and adverse prognosis in patients with infectious diseases [ 18 , 19 ]. Elevated suPAR levels are implicated in different disease settings associated with inflammation including cardiovascular disease, diabetes, rheumatic disease and cancer, whereas suPAR levels may even be predictable of mortality in the general population [ 20 , 21 , 22 ].…”
Section: Discussionsupporting
confidence: 66%
“…In addition, suPAR levels are stable in stored plasma and serum samples, and their quantification is reproducible in samples that have been stored for >5 years at -80 C despite exposure to multiple freeze-thaw cycles [38]. SuPAR has been proposed as a biomarker of immune system activation, and its use is being revised in a variety of diseases, as summarized in Table 1 [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53].…”
Section: Diagnostic Value Of the Upa/upar Systemmentioning
confidence: 99%